Enhancing TCP traffic flow performance with a proportional and integral rate controller: Theory, design, and performance evaluation - Cong, Jun (University of Ottawa (Canada), 2004)
This thesis proposes a new network traffic congestion control algorithm---the PIR (Proportional and Integral Rate) controller. It is designed to overcome the shortcomings of RED and some other related AQM (Active Queue Management) techniques developed in recent years. That is to avoid unnecessary packet losses and stabilize the queue length in the router. It can also prevent the throughput reduction in the presence of wireless links. We proved the stability of the PIR controller theoretically and conducted the performance analysis and comparison for the PIR controller and some other common traffic congestion control schemes.
Keywords: Engineering, Electronics and Electrical.